Memperkuat Jejaring dan Komitmen Kerja Sama untuk Menciptakan Kampus Berkelanjutan - Minarti, Astari; Sunaryo, Thalia; Gunawan, Juniati (Ilin Institute, 2024)
The Sustainability Campus Regional Workshop was conducted as one of the activities to share, increase awareness and knowledge amongst campus stakeholders, both internal and external, in implementing concrete sustainability activities. This activity is expected to increase the collaboration amongst campus members in order to create a balance environmental, social and governance performance. The methods used in this workshop are carried out by delivering materials from related resource people which could be applied into sustainability campus concept. Interactive discussions, questions and answers and sharing experiences amongst participants were conducted. The results showed that the implementation of a sustainable campus is still facing some challenges, such as lifestyle and awareness of the importance of adopting a sustainable mindset is still low. The implementation of sustainable campus concept is currently not optimal. This activity needs to be followed-up by stakeholders and campus leaders, particularly in developing policies and real actions.